Structural performance of nano-silica based blended CFST stub circular column. Issue 1 (November 2020) - Bisht, Himanshu; Gupta, Aakash; Srinivas, Dodda; Adak, Dibyendu
Abstract: The objective of this study is to find the optimum percentage replacement of cement with the nano-silica in a concrete mix to improve the structural performance Concrete Filled Steel Tube (CFST) stub circular column under the axial compressive load. The CFST stub columns with circular cross-sectional area of conventional concrete mix (without nS) and nano-silica blended concrete mix (with nS-CFST) had been experimentally and numerically studied. The amorphous silica is a major component of the cementitious materials, and it reacts with the calcium hydroxide, which is comprised of the calcium silicate hydration. The addition of this nano-silica affects the different properties of the concrete and increases its performance. On the other hand, CFST is known for the composite behavior generated between the hollow tube of steel and a core constructed of concrete, which improves the collected performance of the member. In present study, the concrete mix of M25 had been modified with 4%, 6%, 8% and 10% of nano silica. The structural behavior of stub columns (with / without nS) are assessed under axial compressive load. Also, the CFST stub columns were then modelled into ABAQUS for finite element analysis. The nano-silica blended concrete in CFST stub columns showed an improved the structural performance than the conventional cement concrete stub circular CFST column.